The Effect of Personality Traits on Investors’ Financial Risk Tolerance - Sana Ullah; Muhammad Yusuf Amin; Saeed Akbar, (Dialogue Social Science Review (DSSR), 2025)
Financial risk tolerance is an individual's ability to tolerate and accept a particular level of risk linked with financial decisions. The personality traits are different characteristics that differentiate one person from another based on their financial risk tolerance. As a result, financial advisers and asset managers must assess a client's financial risk tolerance and recommend products based on that level. Hence, this study is designed to check whether the differences in demographics and personality traits influence investors' financial risk tolerance. . The objective of this research is to examine if personality traits impact people's financial risk tolerance. For this study, 200 respondents were selected using the convenience sampling approach. The data was examined with SPSS to evaluate the relationship between the dependent and independent variables. Furthermore, the study discovered a positive and significant association between financial risk tolerance and personality traits such as extroversion and openness to experience. However, neuroticism, conscientiousness, agreeableness, does not show a negative significant relationship. These findings highlight the need to take into consideration individual differences when estimating risk tolerance and giving individualized investment advice. Asset managers and financial advisors can utilize this information to understand investors risk preferences better and develop strategies that match their personal need.